1991
DOI: 10.4049/jimmunol.146.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Human B cells secrete predominantly lambda L chains in the absence of H chain expression.

Abstract: Ig H and L chains are independently assembled in B cells and then secreted together as a functional protein. H chains cannot be secreted without assembly to L chains; however, L chains can be secreted in the absence of H chains by both mice and human cells. To examine the influence of H chain expression on human L chain isotype selection (kappa or lambda), we compared the kappa/lambda ratio of L chains unassociated with H chains (free L chains) to the kappa/lambda ratio of L chains associated with H chains. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…We also observed that wt LC was secreted in both monomeric and dimeric forms, while C κ was secreted as a dimer ( Figure 4C , lanes 1). It is intriguing that wt LC is secreted as a mixture of these two forms, contrary to previous reports that some LCs are secreted as dimers ( Leitzgen et al, 1997 ) while others are monomers ( Ambrosino et al, 1991 ; Dul et al, 1996 ; Skowronek et al, 1998 ). Secretion of single C κ domains was observed at a level barely detectable in the absence of HC expression, unlike wt LC (V κ -C κ ).…”
Section: Resultscontrasting
confidence: 74%
See 1 more Smart Citation
“…We also observed that wt LC was secreted in both monomeric and dimeric forms, while C κ was secreted as a dimer ( Figure 4C , lanes 1). It is intriguing that wt LC is secreted as a mixture of these two forms, contrary to previous reports that some LCs are secreted as dimers ( Leitzgen et al, 1997 ) while others are monomers ( Ambrosino et al, 1991 ; Dul et al, 1996 ; Skowronek et al, 1998 ). Secretion of single C κ domains was observed at a level barely detectable in the absence of HC expression, unlike wt LC (V κ -C κ ).…”
Section: Resultscontrasting
confidence: 74%
“…Conversely, most LCs can be secreted in free form without the need for HC assembly ( Ambrosino et al, 1991 ; Dul et al, 1996 ; Leitzgen et al, 1997 ; Skowronek et al, 1998 ). While certain LCs require dimerization for proper folding and secretion ( Leitzgen et al, 1997 ), many LCs can be secreted as monomers ( Ambrosino et al, 1991 ; Dul et al, 1996 ; Skowronek et al, 1998 ). Most free LCs bind transiently to BiP through their V L domain, in contrast to HCs where BiP associates stably with unfolded and reduced C γ1 .…”
Section: Introductionmentioning
confidence: 99%